Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises: 51

Answer

$-\frac{1}{27x^{3}}$

Work Step by Step

According to the negative exponent rule, $a^{-n}=\frac{1}{a^{n}}$. Therefore, $(-3x)^{-3}=\frac{1}{(-3x)^{3}}=\frac{1}{(-3)^{3}x^{3}}=\frac{1}{-27x^{3}}=-\frac{1}{27x^{3}}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.